Transient severe hypotonic hyponatraemia in children – presentation of three cases - Joanna A. Chrzanowska; Julia Wodniakowska; Aleksander Basiak; Agnieszka Zubkiewicz-Kucharska; Robert Śmigiel (Pediatric Endocrinology, Diabetes and Metabolism)
Hyponatraemia, defined as sodium concentration below 135 mmol/l, is one of the most common electrolyte imbalances. Differential diagnosis of hyponatraemia is difficult. We describe 3 cases of children with transient, severe hyponatraemia (< 125 mmol/l). While diagnosing hyponatraemia, it is of major importance to carefully ask in the anamnesis about habits related to the amount of fluid intake and the type of consumed fluids. It should also be noted that a frequent procedure during an infection is to increase fluid ingesting as a prevention of dehydration. One, however, should remember about the possibility of inducing water poisoning in a patient consuming excessive amounts of hypotonic fluids, especially when exposed to non-osmotic antidiuretic hormone stimulus, such as an acute infection or stress, and/or reduced renal excretory capacity. Only the presence of polyuria does not justify a diagnosis of arginine vasopressin deficiency (AVP-D), and especially the implementation of desmopressin treatment before all diagnostic procedures are completed, specifically in the case of hyponatraemia. Desmopressin can be used simultaneously with intravenous 3% saline solution only in the treatment of a very severe hyponatraemia, to avoid overcorrection of natraemia. In patients after profound hyponatraemia, polyuria can be observed after normalisation of fluid intake, but it is temporary.